Donor white‐blood‐cell survival (microchimerism) following red‐blood‐cell transfusion in Australian patients with burn. (15th January 2019) - Hirani, Rena; Taggart, Susan; Maitz, Peter; Irving, David O.
Abstract : Background: Donor white‐blood‐cell (leucocyte) engraftment, also known as transfusion‐associated microchimerism (TAM), remains a potential outcome for some patients who receive a red‐blood‐cell (RBC) transfusion. Australia introduced universal leucocyte filtration of RBC components in October 2008. However, preceding studies in major trauma patients indicate that filtration does not eliminate the potential of TAM following blood transfusion. Any potential for TAM in other patient groups has not been previously characterized. This study aimed to analyse if TAM could be detected in burn patients. Study design and methods: Australian burn patients were recruited with injury composing of total body surface area (TBSA) ≥15% and who had been transfused with at least one RBC unit between 1 January 2000 to 31 December 2011. The incidence of TAM was determined using a panel of 12 bi‐allelic insertion/deletion polymorphisms. Results: This patient cohort ( n = 8) had median TBSA burn of 34% [15–70%], were transfused with median 9·5 RBC units [1–31] and had median hospital length of stay of 29 days [21–51]. Half of these patients had been transfused with universally leucodepleted RBCs. One patient who received leucodepleted RBC units showed an insertion/deletion pattern indicating the presence of TAM. Conclusion: The detection of TAM in burn patients has not previously been described. In the cohort studied here, TAM was detected in one of the eight patients analysed. Even though leucodepleted blood products were used in some of the analysed patients, TAM appears to remain a potential transfusion‐related outcome.